Words and Images in Maleficent: Mistress of Evil Movie: A Multimodal Discourse Analysis - Lindra Mayu Asis; La Aso; Neil Amstrong (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2021)
This research is about analyzing the words and images in Maleficent: Mistress of Evil movie. To analyze this research, the researcher uses the theory by Kress & Van Leeuwen (2006) to analyze verbal and visual elements in the framework of proposing a comprehensive and systemic interpretation of meaning. This research objective is to determine how words and images are used and related meaning among them. This research uses qualitative description to discuss the two meanings of verbal and visual modes in the Maleficent: Mistress of Evil movie. The types of data analysis are presenting the data, describing the data, finding out the relationship between the meaning of words and the meaning of images, and concluding the data. The researcher found that the dominant used on Mental Processes in the words component. While images were analyzed using only three elements which are on the body of the actors in Maleficent movie such as facial expressions dominant in the feeling happy, gestures dominate when characters stand up straight has meaning confidence, and clothing color dominant the black colors have meaning sadness and 4 data were interrelated for relationships meaning among the modes. The researcher found that this research shows a movie that brings ideology for the community not to judge someone only from their outward appearance and for women to have the power so that they are not easily oppressed.